The Role of Islamic Economic Law in Promoting Entrepreneurship Based on Islamic Values at Tasikmalaya - Mariana, Rani (Doctoral Program of Social Science Pasundan University, 2025)
The role of Islamic Economic Law in promoting entrepreneurship based on Islamic values in Tasikmalaya is an important topic in the region’s economic development. Islamic Economic Law, which is grounded in Sharia principles, provides clear guidance for conducting economic activities in an ethical and sustainable manner. This study aims to analyze how Islamic Economic Law can support the development of entrepreneurship in Tasikmalaya, with a focus on the application of Islamic values in business practices. Concepts such as justice, transparency, and the prohibition of usury (riba) and harmful practices serve as the main foundation in building entrepreneurship that is not only economically profitable but also socially and morally beneficial for the community. The results of the study indicate that the application of Islamic Economic Law can create a conducive environment for entrepreneurs to grow based on just principles, as well as reduce social and economic inequalities in society. Moreover, entrepreneurship based on Islamic values also raises social awareness and responsibility among business actors, which in turn can strengthen the local economy. Thus, Islamic Economic Law can be an essential instrument in creating an entrepreneurial ecosystem based on Islamic moral and ethical values, which benefits not only individuals but also the community as a whole.